Evaluating cephalomedullary fixation for intertrochanteric femur fracture using a validated osteoporotic model - Lee, Yi Feng (Nanyang Technological University, 2024)
Hip fractures, notably femur fractures, pose a significant challenge, particularly within the elderly demographic, often exacerbated by conditions such as osteoporosis. One specific type of hip fracture, known as an intertrochanteric fracture, affects the upper part of the femur and is associated with a considerable 1-year mortality rate. Surgeons often employ cephalomedullary fixation, a surgical technique involving the insertion of a specialized titanium rod, proximal femoral nail antirotation (PFNA-II), to stabilize the fractured bone. However, complications arise when the fractured bone, particularly the lesser trochanter (LT) fragment, extends downward along the femur, away from its original position near the hip joint. As the length of the fracture extension increases, the bone's stability diminishes under loading conditions. This poses a challenge, as the commonly used short PFNA-II may prove inadequate in providing stability when the LT fragment extends significantly, potentially necessitating the use of the long PFNA-II, albeit with higher risks of complications. This study aims to conduct axial loading simulations on the PFNA implant and evaluate the vertical reaction force, axial stiffness, and the von Mises stress at each distal extension length. The simulation was done on a new osteoporotic bone model at the baseline and on the previous osteoporotic bone model with distal extensions of 30 mm and 40 mm. Despite rigorous efforts, the study did not yield significant results, possibly due to inherent limitations in the experimental setup or analytical methods employed. Moving forward, this outcome shows the need for further exploration and refinement of research methodologies to uncover meaningful insights.